2015
DOI: 10.3390/nu7031480
|View full text |Cite
|
Sign up to set email alerts
|

Salacinol and Related Analogs: New Leads for Type 2 Diabetes Therapeutic Candidates from the Thai Traditional Natural Medicine Salacia chinensis

Abstract: The antidiabetic effect of a hot water extract of stems of Salacia chinensis (SCE) was evaluated in vivo in KK-Ay mice, a typical type 2 diabetes mellitus mice model. Administration of CE-2 dietary feed containing 0.25 and/or 0.50% of SCE for three weeks to KK-Ay mice significantly suppressed the elevation of both blood glucose and HbA1c levels without significant changes in body weight or food intake. Glucose tolerance was improved by administration to KK-Ay mice for 27 days of AIN93M purified dietary feed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
(39 reference statements)
0
43
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Several coumarins, [1][2][3][4][5][6][7] xanthones, 8,9) triterpenoids, 10) and steroids 10) have been isolated from the flowers, 1,2,6,7,10) seeds, 3,9) twigs, 4,8) and bark 5) of this plant. In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Several coumarins, [1][2][3][4][5][6][7] xanthones, 8,9) triterpenoids, 10) and steroids 10) have been isolated from the flowers, 1,2,6,7,10) seeds, 3,9) twigs, 4,8) and bark 5) of this plant. In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells.…”
mentioning
confidence: 99%
“…In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells. 1) Further studies revealed that the methanol extract inhibited enzymatic activity against aromatase.…”
mentioning
confidence: 99%
“…Thus, it is clear that the stereochemistry at the different stereogenic centers on the side chain plays a signicant role in biological activity. It appears that the compounds containing the S conguration at C-2 0 , the R conguration at C-4 0 , and the S conguration at C-5 0 are the most active in the sulfur series of compounds; however, that in the selenium series the activities of the selenium analogues, (52) and (53), suggest that the stereochemistry at C-5 0 could be R. The stereochemistry at C-3 0 was judged to be unimportant but can be xed as S to reect a presumed common biosynthetic pathway as salacinol. However, the overall conclusion was that the effect of the acyclic chain extension did not confer any dramatic change on inhibitory properties for this particular enzyme, because the K i values of the active chain-extended analogues were in a similar range to those of salacinol (5) (0.19 mM) and blintol (16) (0.49 mM).…”
Section: Fig 13mentioning
confidence: 99%
“…Therefore improving postprandial hyperglycemia may form part of the strategy for the prevention and management of cardiovascular disease in diabetes. 136) We previously reported that several antidiabetogenic therapeutic candidates were obtained from natural resources such as Kochia scoparia, 137) Borassus flabellifer, 138) Solanum lycocarpum, 139) Sinocrassula indica, 140) Shorea roxburghii, 141) Helichrysum arenarium, 142) and Salacia reticulata, S. oblonga, and S. chinensis [143][144][145][146][147][148] evaluated by postprandial hyperglycemia in sugar-loaded rats and/or mice models. In these experiments the effects of the principal phenylethanoid glycosides from the stems of C. tubulosa, echinacoside (28) and acteoside (29), on postprandial increase in blood glucose levels in starch-loaded mice were examined.…”
Section: Glucose Tolerance-improving Activitymentioning
confidence: 99%